2005
DOI: 10.1080/01650250444000441
|View full text |Cite
|
Sign up to set email alerts
|

Relations between Agreeableness and perceived support in family relationships: Why nice people are not always supportive

Abstract: Do more agreeable individuals perceive more support, and are they perceived as more supportive, across all family relationships or only within specific relationships? In a study of 256 Dutch twoparent families with two adolescents, we examine whether links between Agreeableness and support are generalised across relationships or occur within specific relationships. Social Relations Model analyses showed that individuals who perceive their family members as more agreeable perceive more support from family membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 37 publications
5
44
0
Order By: Relevance
“…A single social relations model analysis was then conducted to partition the variance in everyday talk and satisfaction into actor, partner, and relationship effects for each latent construct, respectively (see Figure 1). Although previous researchers using SRM typically allow for correlations among measurement errors for each indicator per rating family member (i.e., Branje et al, 2005;Finkenauer et al, 2004), doing so in the present study would generate a greater number of parameter estimates than those afforded by the sample size, thus producing potentially unreliable parameter estimates. Therefore, the initial model was estimated without any correlations among measurement errors and then modification indices were examined to determine if correlation estimates among measurement errors were needed.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…A single social relations model analysis was then conducted to partition the variance in everyday talk and satisfaction into actor, partner, and relationship effects for each latent construct, respectively (see Figure 1). Although previous researchers using SRM typically allow for correlations among measurement errors for each indicator per rating family member (i.e., Branje et al, 2005;Finkenauer et al, 2004), doing so in the present study would generate a greater number of parameter estimates than those afforded by the sample size, thus producing potentially unreliable parameter estimates. Therefore, the initial model was estimated without any correlations among measurement errors and then modification indices were examined to determine if correlation estimates among measurement errors were needed.…”
Section: Resultsmentioning
confidence: 74%
“…This decision produced 12 observed scores (or frequencies) of everyday talk and 12 of satisfaction (6 relationships × 2 scales; cf. Branje, van Lieshout, & van Aken, 2005;Finkenauer et al, 2004). A single social relations model analysis was then conducted to partition the variance in everyday talk and satisfaction into actor, partner, and relationship effects for each latent construct, respectively (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Branje et al (2004Branje et al ( , 2005 studied bivariate associations between support and personality and did not assess the unique predictive power of individual FFM factors. Furthermore, these authors only focused on PCR ratings by single individuals, which did not allow for a straightforward comparison of parents' and children's ability to predict dyadic PCR quality.…”
Section: Agreeablenessmentioning
confidence: 99%
“…Indeed, empirical research repeatedly found that agreeableness, extraversion, and neuroticism seem to be most strongly related to various forms of social support (e.g., Asendorpf & van Aken, 2003;Branje, van Lieshout, & van Aken, 2005;Swickert, Hittner, & Foster, 2010;von Dras & Siegler, 1997). Briefly, agreeableness refers to social traits that reflect individual differences in the propensity to be altruistic, trusting, modest, and warm (John & Srivastava, 1999).…”
Section: Personality Traits and Perceived Social Supportmentioning
confidence: 99%